Rural Entrepreneurship in Upper Egyptian Communities: Exploring the Intervention of Agri-Tech Startups - Wael Abohamda Hulail, Marwa (AUC Knowledge Fountain, 2025)
Climate change and economic disturbance have changed the state of the world and increased the dependence on digitization in running people's daily life. In Egypt, the economic instability and climate change have affected people’s standard of living, making it challenging to sustain their life, especially in the agriculture sector. Farmers have been affected by the risks of climate change, economic shocks, and trends of digitization, which have impacted their profit, employability, and livelihood. Several Egyptian Agri-tech startups were launched to support the farmers in the digital revolution that came to agriculture, attempting to make a change in the Egyptian farming sector, by adopting digital information technology, from which farmers can depend in running their farming businesses. Using qualitative methods, through in-depth face-to-face interviews with the founding team of 3 startups and 24 Egyptian small-holder farmers from Menia and Beni Sweif, the research discovers the role of Agri-tech startups in changing farmers' practices and how it impacted them and explores the resilience of Egyptian farmers towards the Agri-tech startups as a tool to face the challenges of climate change and economic disturbance. The research study explores how the Agri-tech startups influenced the agricultural practices of farmers, through mobile applications giving climate smart advisory information and e-commerce platforms. Affected by the resilience and social capital theory, it is discovered that the farmers’ resilience and community social capital assists in facing the challenges they face by increasing their profitability, acquiring knowledge about new agricultural practices and market prices, and expanding their market network in Egypt. This in the end enhanced the farmers’ livelihood stability and sustainability.